Presentation Edition No.61 (3) 2018 - Quirós-Arias, Lilliam; Alfaro-Chavarría, Consuelo (Revista Geográfica de América Central., 2018)
35th Conference of Latin Americanist Geographers (CLAG) 2018 was held in San Jose, Costa Rica.